ANALYSIS AND REDESIGN OF SI TOYA WENING APPLICATION USING DESIGN THINKING METHOD - Alfian, Muhammad Ichsan; Irsan, Muhamad; Fathoni, Muhammad Faris (Informatika, Universitas Jenderal Soedirman, 2024)
Si Toya Wening application is an application designed to facilitate Surakarta PDAM customers in making water bill payments, making complaints, and other features. When research was conducted to 155 users, it showed that there were several indications of problems that usability in this application was not going well, such as a less intuitive interface, mismatch of items on the bottom navigation bar, and information blocked by other elements. In order to enhance the usability of this application, redesigning the interface is essential. As a measure of success, usability testing and system usability scale were used to compare the initial appearance and the appearance after being redesigned. The result of this research is a redesigned prototype with the design thinking method which is then tested using SUS to a sample of 83 respondents. SUS parameters are Acceptability ranges, adjective ratings, and grade scale. The final test results will be assessed in comparison to the initial test results. The test results show a significant improvement in application usability. The increase in the SUS score from 62.35 in the first test to 80.69 in the final test shows an improvement in usability. The acceptability range shifted from “MARGINAL LOW” to “ACCEPTABLE,” the adjective ratings improved from “OK” to “EXCELLENT,” and the grade scale rose from category “D” to “B.” This enhancement indicates that the application's usability has significantly improved.